A Robotics Club in High School: an experience report - Freitas, Elias José De Rezende; Guimarães, Marcos Prado; Ramos, João Vitor; Silva Júnior, Carlos Dias Da (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2023: Anais do XV Simpósio Brasileiro de Robótica e XX Simpósio Latino Americano de Robótica, 2023)
Educational Robotics provides a dynamic and effective platform for fostering diverse skills and competencies. In this context, this paper explores creating and implementing a robotics club in a high school. The proposed methodology emphasizes the educational tripod: teaching, research, and extension. Therefore, the paper outlines the club’s conception, the sources of inspiration, and the achieved outcomes within the school and local community. It also highlights the activities and small projects developed by the students and the active participation of the club members in the Brazilian National Robotics Olympics. Furthermore, through student reports and an internal survey, the paper emphasizes the remarkable development of desired competencies, including creativity, teamwork, problem-solving, and computational thinking.